The Further Shore - Philip Kollithanath (Journal of Dharma, 1977)
This book is a collection of two essays on Sannydsa and the Upanishads. The belief in the non-duality of Sannydsa and Brah-mavidya is to account for the structure of the text, which is nothing but those articles, published by Swamy elsewhere, now edited by his disciples posthumously.